C282Y and H63D Mutation Frequencies in a Population from Central Spain. Issue 2 (13th June 2013) - Alvarez, S.; Mesa, M. S.; Bandrés, F.; Arroyo, E.
Abstract : Objectives: To determine the frequency of hereditary hemochromatosis gene mutations, C282Y and H63D, from 125 autochthonous blood donors originating from a Central region of Spain, to provide epidemiological data about HFE gene in the Iberian Peninsula. Methods: DNA extracted from blood samples was analyzed by PCR-RFLP. Restriction enzimes were Snab I and Bcl I for C282Y and H63D, respectively. Results were visualized with Ethidium Bromide staining after gel electrophoresis. Results and discussion: C282Y frequency was 0.02 and that of H63D was 0.16. Result for C282Y mutation falls within the range of variation of the Mediterranean populations. H63D frequency agrees with those reported for other European populations. In both cases frequencies obtained are the lowest of compared Spanish data. Conclusions: This study is useful to compare expected versus presented C282Y and H63D frequencies in Spanish populations and to contribute to the knowledge of Spanish variability, rarely analyzed until now for HFE gene mutations.